Conversion Timing of Following-Up Thermal Recovery Approaches of Post-CHOP for Foamy Extraheavy Oil Reservoirs. (14th December 2021) - Yang, Zhaopeng; Li, Xingmin; Yu, Yang; Xie, Jia; Dong, Yintao
Abstract : The purpose of this study is to determine the optimal conversion timing of follow-up thermal recovery approaches of post-CHOP for foamy extraheavy oil reservoirs. The microscopic visualization experiment and the one-dimensional sand pack experiment are conducted to investigate the influence of temperature on the foamy oil cold production process. According to the experimental results, it can be concluded that the temperature has great influence on foamy oil flow stage during the CHOP process. Therefore, it is necessary to study the optimal conversion timing of follow-up thermal recovery approaches after CHOP for the foamy extraheavy oil reservoir. Based on the analysis of the experimental results, the compositional foamy oil model is established by taking the effect of temperature into consideration. In the numerical model, the conversion timings of different thermal recovery approaches are investigated. The optimal conversion timings for cyclic steam stimulation (CSS) and steam flooding (SF) processes are the moments when the pressure drops to the pseudo-bubble point pressure. For the CSS method, excessive pressure cannot give full play to the production potential of CHOP stage; when the pressure is too low, it lacks enough energy to drive the heated crude oil to the wellbore. For the SF method, high pressure cannot fully release the latent heat of steam, and the content of dissolved gas (which will hinder the heat transfer) in oil phase is higher under high pressure, while the very low pressure leads to relatively high viscosity of crude oil; thus, the performance of the SF process becomes worse. For the SAGD process, the adverse effects of released solution gas in foamy extraheavy oil reservoir outweigh the positive effects. As a result, the CHOP period should be extended as long as possible to obtain a high recovery. In other words, the recovery process should be switched to the SAGD process at a relatively low formation pressure. The findings of this study could help for better understanding of the CHOP and post-CHOP thermal techniques for foamy extraheavy oil reservoirs, and it can provide guidance for reservoir engineers to make better use of the thermal recovery techniques to further improve the recovery performance of foamy extraheavy oil reservoirs.